2020
DOI: 10.3897/mycokeys.72.55445
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Microdochium from Indocalamus longiauritus in south-western China

Abstract: Microdochium species have often been reported as plant pathogens and saprophytes and are commonly isolated from some diseased plant hosts. The primary aim of the present study was to describe and illustrate two new Microdochium species isolated from the leaf spot of Indocalamus longiauritus in Yunnan Province, China, namely Microdochium yunnanense and M. indocalami, spp. nov., based on their morphology and multilocus phylogenetic analyses of the combined ITS, LSU, TUB2, and RPB2. DNA sequence data indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Microdochium species are commonly known as plant pathogens and saprophytes isolated from diseased plant hosts such as grasses and cereals [ 103 ]. The genus is characterized by its spherical and erumpent stromata and solitary transparent spindle-shaped to oval conidia [ 104 ]. Furthermore, Gyoerffyella species are known as aquatic and terrestrial saprobes and pathogens normally found in decaying leaves [ 105–107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Microdochium species are commonly known as plant pathogens and saprophytes isolated from diseased plant hosts such as grasses and cereals [ 103 ]. The genus is characterized by its spherical and erumpent stromata and solitary transparent spindle-shaped to oval conidia [ 104 ]. Furthermore, Gyoerffyella species are known as aquatic and terrestrial saprobes and pathogens normally found in decaying leaves [ 105–107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight new sequences were generated in this study, and available reference sequences of Microdochium species were retrieved from GenBank [ 2 , 3 , 4 , 5 , 6 , 7 ]. Four genetic markers (ITS, LSU, TUB2 and RPB2) were separately aligned using MAFFT v.7.110 (Osaka, Japan) [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…This genus is characterized by spherical and erumpent stromata composed of minute and transparent cells, small papilla, conical sporulation cells and solitary transparent spindle-shaped-to-oval conidia. In recent years, many taxonomists have continuously enriched the known diversity in Microdochium [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Currently, 54 names are listed for this genus in the Index Fungorum [ 9 ], but only 37 species are accepted in the Catalogue of Life [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the interest in golf has led to an increase in grass areas requiring intensive maintenance. The Microdochium genus includes many species that are highly pathogenic, weakly pathogenic, endophytes, and saprophytes on cereals and grasses ( Kirk & Deacon, 1987 ; Hernández-Restrepo, Groenewald & Crous, 2016 ; Demirci & Dane, 2003 ; Hong et al, 2008 ; Lenc et al, 2014 ; Li, Li & Qi, 2019 ; Gagkaeva et al, 2020 ; Huang et al, 2020 ). Pathogenic Microdochium spp.…”
Section: Introductionmentioning
confidence: 99%